2023
DOI: 10.1111/dom.14979
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term cost‐effectiveness analysis of tirzepatide versus semaglutide 1.0 mg for the management of type 2 diabetes in the United States

Abstract: Aim To evaluate the long‐term cost‐effectiveness of tirzepatide (5, 10 and 15 mg doses), a novel glucose‐dependent insulinotropic polypeptide (GIP) and glucagon‐like peptide‐1 (GLP‐1) receptor agonist, versus semaglutide 1.0 mg, an injectable glucagon‐like peptide‐1 receptor agonist, based on the results of the head‐to‐head SURPASS‐2 trial, from a US healthcare payer perspective. Materials and Methods The PRIME Type 2 Diabetes Model was used to make projections of clinical and cost outcomes over a 50‐year time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Observational data suggest a notable under-utilisation of GLP-1 RAs among individuals in lower socioeconomic groups, primarily due to the high cost of these medications, highlighting the disparity in access to effective diabetes treatments based on socioeconomic factors [ 63 ]. From a broader societal perspective, even though s.c. tirzepatide has been suggested to be cost-effective compared with s.c. semaglutide in the USA [ 64 ], cost-effectiveness analyses conducted in low-, middle- and high-income countries have demonstrated that GLP-1 RAs are not cost-effective compared with other glucose-lowering drugs [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Observational data suggest a notable under-utilisation of GLP-1 RAs among individuals in lower socioeconomic groups, primarily due to the high cost of these medications, highlighting the disparity in access to effective diabetes treatments based on socioeconomic factors [ 63 ]. From a broader societal perspective, even though s.c. tirzepatide has been suggested to be cost-effective compared with s.c. semaglutide in the USA [ 64 ], cost-effectiveness analyses conducted in low-, middle- and high-income countries have demonstrated that GLP-1 RAs are not cost-effective compared with other glucose-lowering drugs [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple MAs of the SURPASS trial program have shown that tirzepatide, in a dose-dependent manner, demonstrates superior glycemic efficacy and noticeable reductions in body weight compared to other GLP-1 RAs, while maintaining a satisfactory safety profile [58][59][60]. In particular, two CEAs have indicated that the 5, 10, and 15 mg doses of tirzepatide are likely to be cost-effective compared to the 1.0 mg dose of semaglutide for the treatment of T2DM in the United States [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…This may be particularly important in young-onset T2D where higher rates of obesity, more rapid deterioration in blood glucose levels and earlier development of diabetes complications have been observed [ 9 , 95 ]. Nevertheless, the cost-effectiveness of initiating treatment with the novel molecules for T2D in different populations and at different time points during the disease continuum will require further assessment [ 96 ]. The ongoing SURPASS EARLY study will provide over the next years data on the benefits of early tirzepatide initiation (as second line, after metformin) compared to standard care using gradual escalation of glucose-lowering treatments (NCT05433584).…”
Section: Expert Opinionmentioning
confidence: 99%